Advancement of omics techniques for chemical profile analysis and authentication of milk. (September 2022) - Qin, Chenchen; Liu, Lei; Wang, Yu; Leng, Tuo; Zhu, Mengting; Gan, Bei; Xie, Jianhua; Yu, Qiang; Chen, Yi
Abstract: Background: Milk is one of the most easily adulterated foods, and the fact that its milk composition is influenced by factors such as animal species and processing methods makes the identification of adulterated dairy products even more challenging. Therefore, there is a need for more accurate, faster and comprehensive techniques to address the problem of dairy product adulteration. Scope and Approach: As one of the rapidly developing technologies in recent years, omic techniques have found increasing application for the identification of dairy products due to their high throughput, wide applicability and more accurate reflection of food status. This review provides an important overview of the nutritional characterization and adulteration identification of milk products by omic techniques over the last few years. Key Findings and Conclusions: This paper highlights the differences between different breeds and processing methods of bovine milk from omic perspective, and introduces the scope, advantages and disadvantages of different omic techniques in dairy products. It is found that metabolomics, proteomics and lipid omics are widely used in the study of dairy products, and promising results have been achieved, and it is strongly recommended to apply multiple analysis techniques jointly to enhance the compound coverage and obtain comprehensive information for the future omics studies. Highlights: Reviewed effects of processing and origin on milk components of untarget analysis. Omic technology is increasingly being used in identifying milk adulteration. The benefits and drawbacks of omic techniques in milk analysis were discussed.